1, 3-Butadiene, styrene and selected outcomes among synthetic rubber polymer workers: Updated exposure-response analyses. (25th September 2021) - Sathiakumar, Nalini; Bolaji, Bolanle; Brill, Ilene; Chen, Ligong; Tipre, Meghan; Leader, Mark; Arora, Tarun; Delzell, Elizabeth
Abstract: Objective: – To evaluate exposure-response relationships between 1, 3-butadiene and styrene and selected diseases among synthetic rubber polymer workers. Methods: – 21, 087 workers (16, 579 men; 4508 women) were followed from 1943 through 2009 to determine mortality outcomes. Cox regression models estimated rate ratios (RRs) and 95% confidence intervals (CIs) by quartile of cumulative exposure to butadiene or styrene and exposure-response trends for cancers of the bladder, lung, kidney, esophagus and pancreas, and for all nonmalignant respiratory disease (NMRD), chronic obstructive pulmonary disease (COPD) and pneumonia. Results: – Bladder cancer RRs were 2.13 (95% CI = 1.03 to 4.41) and 1.64 (95% CI = 0.76 to 3.54) in the highest quartiles of cumulative exposure to butadiene and styrene, respectively, and exposure-response trends were positive for both monomers (butadiene, trend p = 0.001; styrene, trend p = 0.004). Further analyses indicated that the exposure-response effect of each monomer on bladder cancer was demonstrated clearly only in the subgroup with high cumulative exposure (at or above the median) to the other monomer. Lung cancer was not associated with either monomer among men. Among women, lung cancer RRs were above 1.0 in each quartile of cumulative exposure to each monomer, but exposure-response was not seen for either monomer. Male workers had COPD RRs slightly above 1.0 in each quartile of cumulative exposure to each monomer, but there was no evidence of exposure-response among the exposed. Monomer exposure was not consistently associated with COPD in women or with the other cancer outcomes. Conclusions: – This study found a positive exposure-response relationship between monomer exposures and bladder cancer. The independent effects of butadiene and styrene on this cancer could not be delineated. In some analyses, monomer exposure was associated with lung cancer in women and with COPD in men, but inconsistent exposure-response trends and divergent results by sex do not support a causal interpretation of the isolated positive associations. Highlights: Positive exposure-response for both butadiene and styrene and bladder cancer. Independent effects of butadiene and styrene on bladder cancer not determined. Monomers not associated consistently with other cancers or respiratory disease.